Earth Science Workshop After Five Years - Winder, C. (Geoscience Canada, 1975)
Summary The earth science workshop at the University of Western Ontario has now completed five summer sessions and over 100 teachers from across Canada have attended. During the last three years, two Canadian teachers have supervised the development of a Canadian program, with emphasis on methodology with development of classroom exercises and field projects. Approximately one-third of the course is devoted to field trips. Visiting speakers discuss relevant matters of current interest. Present financing is provided by Shell Canada Ltd. Although this workshop is providing a need in the short term for earth science teachers, university-trained teachers will be required as the demand for a course on earth science increases at the secondary school level.